PERAN PROGRAM TILAWAH AL-QUR’AN BERBANTUAN METODE UMMI DALAM MENINGKATKAN LITERASI AL-QUR’AN SISWA KELAS 2 SD MODERN EL MUMTAZ RENGEL TUBAN - Novia Ramadani, Dina Cantika; Nurul Hakim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to describe the implementation of the Ummi Method-assisted Al-Qur’an Tilawah program and analyze its role as an Al-Qur’an learning program that enhances Al-Qur’an literacy among 2nd-grade students at SD Modern El Mumtaz Rengel Tuban. Al-Qur’an literacy in this context is defined as the ability to read the Al-Qur’an with tartil, correct makharijul huruf, and proper tajwid. A qualitative descriptive approach was employed, with data collected through observation, in-depth interviews, and documentation. Primary data were sourced from Al-Qur’an teachers and the learning process, while secondary data were obtained from relevant literature. Data analysis involved reduction, presentation, and conclusion drawing, validated through source and technique triangulation. The findings reveal that the Ummi Method Al-Qur’an reading program at SD Modern El Mumtaz is implemented systematically following the standard Ummi stages: opening, apperception, concept implantation-understanding, practice, and evaluation. Classroom learning combines classical and individual methods, enabling gradual and structured processes for students. The Ummi Method significantly contributes to improving students' Al-Qur’an literacy through intensive learning, routine murojaah, and continuous evaluation. Main challenges include variations in students' abilities and concentration levels, as well as limited parental support at home. Overall, the Ummi Method-based Al-Qur’an learning program is effective in enhancing 2nd-grade students' Al-Qur’an literacy. However, synergy between the school and parents is still needed for program optimization